1974
DOI: 10.1021/ic50135a004
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an intramolecular C --H...N hydrogen bond in (E) -5-methylpyridine-2-carboxaldehyde-2'-pyridylhydrazonetetracarbonylmolybdenum(O) from its crystal structure and proton magnetic resonance spectrum

Abstract: Bruce, Cooper, Freeman, and McGrath lower barrier than the one we are observing in the proton nmr) involves motion of the hydride ligand through the plane of the phosphorus nuclei rendering the carbonyls equivalent but still maintaining the distinction between the two types of phosphorus. Efforts to observe this process using 13C nmr have been unsuccessful.In summary, although the distinction is not unambiguous, the results tend to favor permutational set II with an exchange intermediate of sufficient concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1974
1974
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Both inter- and intramolecular hydrogen bonds involving C−H ··· X interactions are well-known. Various methods were applied to establish the presence of hydrogen bonding, among which analysis of short intermolecular contacts in solid state, IR in solution , and in matrix, NMR spectroscopy in solution, , and quantum mechanical calculations 14,21,22,25-27 should be mentioned.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both inter- and intramolecular hydrogen bonds involving C−H ··· X interactions are well-known. Various methods were applied to establish the presence of hydrogen bonding, among which analysis of short intermolecular contacts in solid state, IR in solution , and in matrix, NMR spectroscopy in solution, , and quantum mechanical calculations 14,21,22,25-27 should be mentioned.…”
Section: Introductionmentioning
confidence: 99%
“…There are several experimental NMR evidences of intramolecular hydrogen bonds involving methylene, methine, and vinylic C−H groups. ,,, Thus, the hydrogen bonds involving strongly activated methine protons in derivatives ( 1 ) were shown to promote stabilization of the six-membered rings in solution . The α-proton of the vinyl group attached to a heteroatom (O, N, S) was shown to form a hydrogen bond with the neighboring donor atoms in various heterocyclic derivatives of which compound 2 is a representative example. , However, the experimental data on the aromatic C−H ··· X interactions are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Further evidence was provided by its 13 C NMR spectrum, where two resonances due to C6 and C6′ of 2,2′-bipyridine were observed as magnetically nonequivalent resonances at δ156.9 ( 1 J C–H = 191 Hz) and 150.6 ( 1 J C–H = 186 Hz). A similar downfield shift and large 1 J C–H value were reported for 2-(1-vinyl-1 H -pyrrol-2-yl)­pyridine, which has an intramolecular hydrogen bond between the hydrogen atom bound to the vinyl group and the nitrogen atom of the pyridine moiety Figure shows the mononuclear structure of 4a , in which the tantalum atom possesses a six-coordinate pseudo-octahedral geometry with the 2-pyridylimido ligand and one of two nitrogen atoms of the 2,2′-bipyridine ligand at the axial positions.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Figure shows the mononuclear structure of 4a , in which the tantalum atom possesses a six-coordinate pseudo-octahedral geometry with the 2-pyridylimido ligand and one of two nitrogen atoms of the 2,2′-bipyridine ligand at the axial positions. Additionally, the nitrogen atom, N2, of the pyridyl ring points toward H6 bound to C6 with the N2···C6 distance (3.289 Å), which lies in the range of weak hydrogen bond distances . Although the bond distance of Ta–N1 (1.782(9) Å) and the angle of Ta–N1–C1 (173.9(7)°) are normal for typical 6e-donating imido ligands, the 2-pyridylimido ligand is slightly bent toward the C6 of 2,2′-bipyridine.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Compounds with divalent transition metals, such as Cu 2+ , Zn 2+ , Co 2+ , Ni 2+ and Ru 2+ (Ghosh et al, 2011(Ghosh et al, , 2013Rojo et al, 1988;Chaur et al, 2011;Chiumia et al, 1999;Stadler et al, 2010), have been observed. Also, these kinds of derivatives are found coordinated to metals such as Pb 2+ , Yb 3+ , Hg 2+ and Mo 0 Baraniak et al, 1976;Bruce et al, 1974). The crystallographic data of only a few organic compounds derived from 2-hydrazinylpyridine have been reported (13 hits).…”
Section: Introductionmentioning
confidence: 99%